Management of Christian Spiritual Programs to Improve Students’ Religious Character - Nonita Barus; Alpino Susanto; Linayati Lestari (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the management of Christian spiritual programs to improve students’ religious character at SMKS Multistudi High School, Batam. The research used a mixed methods approach with a sequential explanatory design. Quantitative data were obtained through questionnaires completed by 41 students, while qualitative data were collected through interviews with the principal, the vice principal for student affairs, the Christian Religious Education teacher, and the Rohkris advisor, as well as activity documentation. Quantitative analysis used descriptive statistics, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The research results showed that students’ religious character was in the good to very good category, indicated by increased discipline, responsibility, politeness, and social concern. The findings indicate that the improvement in religious character was influenced by program management, including structured planning, clear task distribution, habit-based implementation, and continuous evaluation. Programs integrated with Christian Religious Education strengthened the internalization of values in school life. Thus, the quality of spiritual program management became the main factor in the success of shaping students’ religious character, not simply the existence of religious activities